Modified cyclodextrin metal framework material, dealcoholized silicone sealant capable of being coated and preparation method of dealcoholized silicone sealant

By modifying the cyclodextrin metal frame material and blending the components, a fast-solid dealcohol type silicone sealant that can be coated and stored is prepared, which solves the problems of slow curing speed and poor storage stability. in the field of prefabricated construction.

CN119285984APending Publication Date: 2025-01-10GUANGZHOU BAIYUN CHEM IND +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411674185.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing dealcoholized silicone sealant releases small alcohol molecules during the curing process, resulting in poor storage stability, slow curing speed, and inability to apply, limiting its application in the field of prefabricated buildings.

Method used

By modifying the cyclodextrin metal frame material with acryloyloxy-containing silane, blending it with alkoxy-terminated 107 glue, dimethyl silicone oil and other components, adding a crosslinking agent and a catalyst to prepare a A fast-resolution dealcohol type silicone sealant that can be applied and stored stable.

Benefits of technology

It significantly improves the coatingability and storage stability of dealcoholic silicone sealant, shortens the surface drying time, and improves the deep curing speed. It is suitable for prefabricated construction fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146632870000021
    Figure BDA0005146632870000021
  • Figure BDA0005146632870000061
    Figure BDA0005146632870000061
  • Figure BDA0005146632870000062
    Figure BDA0005146632870000062
Patent Text Reader

Abstract

The invention relates to a modified cyclodextrin metal framework material, a dealcoholized silicone sealant capable of being coated and a preparation method of the dealcoholized silicone sealant. The modified cyclodextrin metal framework material is obtained by modifying a cyclodextrin metal framework material by using silane containing acryloyloxy. The dealcoholized silicone sealant is prepared from the following raw materials in parts by mass: 100 parts of alkoxy terminated 107 glue; 20 to 50 parts of dimethyl silicone oil; 20-90 parts of a modified cyclodextrin metal framework material; 100 to 200 parts of an inorganic filler; 0.5 to 1.5 parts of a cross-linking agent; 0.2 to 1.0 part of a coupling agent; and 2-8 parts of a titanate catalyst. The modified cyclodextrin metal framework material is prepared by modifying the cyclodextrin metal framework material with the acryloyloxy-containing silane, and then the modified cyclodextrin metal framework material is used for preparing the dealcoholized silicone sealant, so that the obtained dealcoholized silicone sealant has excellent coating performance, storage stability and deep curing speed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sealants, and specifically relates to a modified cyclodextrin metal frame material, a storage-stable, rapidly curable, coatable dealcoholized silicone sealant, and a preparation method thereof. Background Art

[0002] The dealcoholized silicone sealant releases small alcohol molecules during the curing process. It is green and environmentally friendly, non-corrosive to metal substrates, has wide adhesion to substrates, and has good weather resistance and high and low temperature resistance. It has always attracted much attention.

[0003] In the field of prefabricated buildings, the main body of the building needs to be exposed to wind and sun for a long time, so the caulking and sealing materials are required to have good weather resistance. The best choice is undoubtedly silicone sealant with good weather resistance. However, the exterior walls of prefabricated buildings often need to be painted to ensure the same color of the building appearance. Silicone sealants have to be abandoned due to their low surface energy and poor paintability. Then, silane-modified polyether glue with good paintability but relatively weak weather resistance and high price is chosen. For this reason, if a dealcoholized silicone sealant with paintability can be developed, it will have a large market demand.

[0004] In addition, dealcoholized silicone sealant has the disadvantages of slow curing speed and poor storage stability. Its curing performance will be significantly reduced during long-term storage, and it may even fail to cure at all. These disadvantages also restrict its further promotion.

[0005] Therefore, it is necessary to prepare a paintable, storage-stable fast-curing dealcohol-free silicone sealant. Summary of the invention

[0006] Based on this, the object of the present invention is to provide a paintable, storage-stable, fast-curing dealcoholized silicone sealant.

[0007] The technical solutions for achieving the above-mentioned purpose include the following.

[0008] In a first aspect, the present invention provides a modified cyclodextrin metal framework material obtained by modifying the cyclodextrin metal framework material with acryloxy-containing silane.

[0009] Wherein, the acryloxy-containing silane is selected from at least one of 3-(acryloxy)propyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propyltriisopropoxysilane, and methacryloxypropyltriacetoxysilane; the cyclodextrin in the cyclodextrin metal frame material is one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin.

[0010] The cyclodextrin metal framework material can be prepared by the following method: filtering an aqueous solution containing cyclodextrin and potassium hydroxide into a first alcohol solvent, allowing the solution to stand at 40°C-60°C for 4h-8h, adding hexadecyltrimethylammonium bromide, stirring evenly, and allowing the solution to stand at 20°C-30°C for 8h-24h to obtain the cyclodextrin metal framework material.

[0011] In a second aspect, the present invention provides a method for preparing the modified cyclodextrin metal framework material, comprising the following steps:

[0012] The cyclodextrin metal framework material is added to the second alcohol solvent and dispersed evenly, and then the acryloxy-containing silane and NH3·H2O are added, and the mixture is stirred and reacted at 50° C.-80° C. for 3 h-6 h to obtain the modified cyclodextrin metal framework material.

[0013] In a third aspect, the present invention provides a dealcoholized silicone sealant, wherein the dealcoholized silicone sealant is prepared from raw materials including the following components, in parts by mass:

[0014]

[0015] In a fourth aspect, the present invention provides a method for preparing the dealcoholized silicone sealant, comprising the following steps:

[0016] The alkoxy-terminated 107 glue, dimethyl silicone oil, modified cyclodextrin metal frame material and inorganic filler are dehydrated and blended at a temperature of 90°C to 130°C and a vacuum degree of -0.08MPa to -0.099MPa for 60min to 180min, cooled to 40°C to 50°C, and the cross-linking agent, coupling agent and catalyst are added. The mixture is mixed and reacted for 40min to 120min at a vacuum degree of -0.08 to -0.099MPa and a stirring speed of 100rpm to 800rpm to obtain the dealcoholized silicone sealant.

[0017] The present invention has the following beneficial effects:

[0018] The present invention uses acryloxy-containing silane to modify cyclodextrin metal frame materials to prepare a modified cyclodextrin metal frame material, and then the modified cyclodextrin metal frame material is combined with alkoxy-terminated 107 glue, dimethyl silicone oil and other components to prepare a paintable, storage-stable, fast-curing dealcoholized silicone sealant. The acryloxy-containing silane on the surface of the modified cyclodextrin metal frame material can react with the acrylate monomer in the coating, thereby significantly improving the paintability of the dealcoholized silicone sealant. At the same time, the addition of the modified dextrin metal frame material can significantly improve the storage stability of the dealcoholized silicone sealant and increase the deep curing speed of the dealcoholized silicone sealant.

[0019] The dealcoholized silicone sealant provided by the present invention has excellent paintability, excellent storage stability and deep curing speed, short surface drying time, fast curing speed and greatly improved curing depth, and can be applied in the field of prefabricated buildings.

[0020] By optimizing the specific selection and proportion of each preparation raw material, the coating performance, storage stability and deep curing speed of the obtained alcohol-based silicone sealant are further improved.

[0021] The preparation methods of the modified cyclodextrin metal frame material and the dealcoholized silicone sealant provided by the invention are simple and conducive to industrial production. DETAILED DESCRIPTION

[0022] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0023] The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or conditions recommended by the manufacturers. The various commonly used chemical reagents used in the examples are all commercially available products.

[0024] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.

[0025] In addition, as used in the present invention, the term "or" is an inclusive "or" symbol and is equivalent to the term "and / or", unless the context clearly dictates otherwise. The term "based on" is not exclusive and allows for being based on other factors not described, unless the context clearly dictates otherwise. In addition, throughout the specification, the meanings of "a", "an", and "the" include plural referents. The meaning of "in..." includes "in..." and "on...".

[0026] Some of the embodiments relate to a modified cyclodextrin metal framework material, which is prepared by modifying the cyclodextrin metal framework material with acryloxy-containing silane.

[0027] In some preferred embodiments, the acryloxy-containing silane is selected from at least one of 3-(acryloxy)propyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propyltriisopropoxysilane and methacryloxypropyltriacetoxysilane.

[0028] In some preferred embodiments, the cyclodextrin in the cyclodextrin metal framework material is one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin.

[0029] In some preferred embodiments, the mass ratio of the acryloxy-containing silane to the cyclodextrin metal framework material is 2-6:1, preferably 3-5:1, and more preferably 3.5-4.5:1.

[0030] In some preferred embodiments, the preparation method of the cyclodextrin metal frame material comprises the following steps: filtering an aqueous solution containing cyclodextrin and potassium hydroxide into a first alcohol solvent, allowing to stand at 40°C-60°C for 4h-8h, adding hexadecyltrimethylammonium bromide, stirring evenly, and allowing to stand at 20°C-30°C for 8h-24h to obtain the cyclodextrin metal frame material.

[0031] In some preferred embodiments, the mass ratio of cyclodextrin, potassium hydroxide and hexadecyltrimethylammonium bromide is 1g:0.3g-0.4g:0.2mg-0.6mg, preferably 1g:0.2g-0.5g:0.3mg-0.5mg.

[0032] In some preferred embodiments, the concentration of cyclodextrin in the aqueous solution is 25 g / L to 40 g / L, preferably 30 g / L to 35 g / L.

[0033] In some preferred embodiments, the volume ratio of the first alcohol solvent to water is 1:0.8-1.2.

[0034] In some preferred embodiments, the first alcohol solvent is methanol or ethanol.

[0035] In some preferred embodiments, the preparation method of the cyclodextrin metal frame material comprises the following steps: dissolving the cyclodextrin and potassium hydroxide in water, filtering the resulting solution into a reaction kettle filled with methanol, allowing it to stand at 40°C-60°C for 4h-8h (preferably allowing it to stand at 45°C-55°C for 4h-6h), adding the hexadecyltrimethylammonium bromide, stirring evenly, allowing it to stand at 20°C-30°C for 8h-24h (preferably 12h-16h), filtering, washing, and drying to obtain the cyclodextrin metal frame material.

[0036] In some preferred embodiments, the drying is performed under vacuum conditions at 40°C-60°C.

[0037] In some embodiments, the method for preparing the modified cyclodextrin metal framework material of the present invention comprises the following steps:

[0038] The cyclodextrin metal framework material is added to the second alcohol solvent and dispersed evenly, and then the acryloxy-containing silane and NH3·H2O are added, and the mixture is stirred and reacted at 50° C.-80° C. for 3 h-6 h to obtain the modified cyclodextrin metal framework material.

[0039] In some preferred embodiments, the second alcohol solvent is methanol or ethanol.

[0040] In some preferred embodiments, the ratio of the cyclodextrin metal framework material to the second alcohol solvent is 1 g: 20 mL-50 mL, preferably 1 g: 30 mL-40 mL.

[0041] In some preferred embodiments, the ratio of the cyclodextrin metal framework material to NH3·H2O is 1 g: 2 mL-5 mL, preferably 1 g: 3 mL-4 mL.

[0042] In some preferred embodiments, the method for preparing the modified cyclodextrin metal framework material comprises the following steps:

[0043] The cyclodextrin metal framework material is added to anhydrous ethanol, ultrasonically stirred for 60 min-90 min, and then the acryloxy-containing silane and NH3·H2O are added, stirred and reacted at 50°C-80°C for 3h-6h, filtered, washed, and dried to obtain the modified cyclodextrin metal framework material.

[0044] In some preferred embodiments, the reaction is preferably stirred at 65° C.-75° C. for 3 h-4 h.

[0045] In some preferred embodiments, the drying is carried out under vacuum conditions at 50°C-60°C.

[0046] Some of the embodiments also involve a dealcoholized silicone sealant, which is prepared from raw materials including the following components in parts by mass:

[0047] 100 parts of alkoxy-terminated 107 glue;

[0048] 20-50 parts of dimethyl silicone oil;

[0049]

[0050] In some preferred embodiments, the dealcoholized silicone sealant is prepared from raw materials including the following components, in parts by mass:

[0051]

[0052] In some preferred embodiments, the dealcoholized silicone sealant is prepared from raw materials including the following components, in parts by mass:

[0053]

[0054] In some preferred embodiments, the alkoxy-terminated 107 gum is at least one of methyl dimethoxy-terminated 107 gum, methyl diethoxy-terminated 107 gum, vinyl dimethoxy-terminated 107 gum, vinyl diethoxy-terminated 107 gum, trimethoxy-terminated 107 gum and triethoxy-terminated 107 gum.

[0055] In some preferred embodiments, the viscosity of the alkoxy-terminated 107 glue at 25° C. is 10000 mPa·s to 100000 mPa·s.

[0056] In some preferred embodiments, the viscosity of the alkoxy-terminated 107 glue at 25° C. is 15000 mPa·s to 25000 mPa·s.

[0057] In some preferred embodiments, the viscosity of the dimethyl silicone oil at 25° C. is 100 mPa·s to 500 mPa·s.

[0058] In some preferred embodiments, the viscosity of the dimethyl silicone oil at 25° C. is 300 mPa·s to 400 mPa·s.

[0059] In some preferred embodiments, the inorganic filler is at least one of nano-active calcium carbonate, light calcium carbonate and heavy calcium carbonate.

[0060] In some preferred embodiments, the crosslinking agent is at least one of methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane and phenyltrimethoxysilane.

[0061] In some preferred embodiments, the coupling agent is at least one of γ-aminopropyltrialkoxysilane, N-(β-aminoethyl)-γ-aminopropyltrialkoxysilane, γ-glycidoxypropyltrialkoxysilane, γ-mercaptopropyltrimethoxysilane and 3-isocyanatepropyltrialkoxysilane.

[0062] In some preferred embodiments, the titanate catalyst is selected from at least one of tetraisopropyl titanate, tetrabutyl titanate, diisopropyl di(ethyl acetoacetate) titanate, dibutoxybis(ethyl acetoacetate) titanate and diisobutyl di(ethyl acetoacetate) titanate.

[0063] Some of the embodiments involve a method for preparing the dealcoholized silicone sealant of the present invention, comprising the following steps:

[0064] The alkoxy-terminated 107 glue, dimethyl silicone oil, modified cyclodextrin metal frame material and inorganic filler are dehydrated and blended at a temperature of 90°C to 130°C and a vacuum degree of -0.08MPa to -0.099MPa for 60min to 180min, cooled to 40°C to 50°C, and the cross-linking agent, coupling agent and catalyst are added. The mixture is mixed and reacted for 40min to 120min at a vacuum degree of -0.08 to -0.099MPa and a stirring speed of 100rpm to 800rpm to obtain the dealcoholized silicone sealant.

[0065] The present invention is further described in detail below with reference to specific embodiments.

[0066] In the following examples, unless otherwise specified, "parts" refer to parts by weight.

[0067] In the following examples, unless otherwise specified, the viscosity mentioned refers to the viscosity tested at 25°C.

[0068] Example 1

[0069] 162g of γ-cyclodextrin and 56g of potassium hydroxide were dissolved in 5.0L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 4.5L of methanol. After standing and diffusing at 50°C for 5h, 66.5mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 25°C for 12h. The solution was filtered, and the obtained crystals were washed twice with 1.5L of methanol, and then dried under vacuum at 50°C to obtain a cyclodextrin metal framework material (γ-CD-MOF).

[0070] 60 g of γ-CD-MOF was added to 2.0 L of anhydrous ethanol and ultrasonically stirred for 60 min. Then, 250 g of 3-(acryloyloxy)propyltrimethoxysilane and 200 mL of NH3·H2O were added to the ethanol dispersion, and the reaction was stirred at 70°C for 3 h. The residue was filtered and washed twice with 1.0 L of anhydrous ethanol and dried under vacuum at 60°C to obtain a modified cyclodextrin metal framework material (M-γ-CD-MOF-1).

[0071] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 70 parts of M-γ-CD-MOF-1, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0072] Example 2

[0073] 100 g of α-cyclodextrin and 35 g of potassium hydroxide were dissolved in 3.0 L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 3.0 L of methanol. After standing and diffusing at 60 ° C for 4 hours, 40 mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 30 ° C for 18 hours. The above solution was filtered, and the obtained crystals were washed twice with 1.0 L of methanol, and then dried under vacuum conditions at 60 ° C to obtain a cyclodextrin metal framework material (α-CD-MOF).

[0074] 50g of α-CD-MOF was added to 1.5L of anhydrous ethanol and ultrasonically stirred for 70min. Then, 200g of 3-(methacryloyloxy)propyltrimethoxysilane and 150mL of NH3·H2O were added to the ethanol dispersion and stirred for reaction at 80°C for 3h. The residue was filtered and washed twice with 1.0L of anhydrous ethanol and dried under vacuum at 50°C to obtain the modified cyclodextrin metal framework material (M-α-CD-MOF-2).

[0075] 100 parts of methyl diethoxy-terminated 107 glue with a viscosity of 50000 mPa·s, 20 parts of dimethyl silicone oil with a viscosity of 500 mPa·s, 40 parts of M-α-CD-MOF-2, and 100 parts of light calcium carbonate were dehydrated and blended at a temperature of 130°C and a vacuum degree of -0.090 MPa for 60 minutes. After being fully cooled to 50°C, 0.5 parts of methyl triethoxy silane, 1.0 parts of γ-glycidyloxypropyl trimethoxy silane and 8 parts of dibutoxy bis(ethyl acetoacetate) titanate were added, and the mixture was mixed and reacted for 120 minutes at a vacuum degree of -0.085 MPa and a stirring speed of 100 rpm to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0076] Example 3

[0077] 200 g of β-cyclodextrin and 70 g of potassium hydroxide were dissolved in 6.0 L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 5.0 L of methanol. After standing and diffusing at 40 ° C for 8 hours, 85 mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 25 ° C for 24 hours. The above solution was filtered, and the obtained crystals were washed twice with 2.0 L of methanol, and then dried under vacuum conditions at 40 ° C to obtain a cyclodextrin metal framework material (β-CD-MOF).

[0078] 100 g of β-CD-MOF was added to 4.0 L of anhydrous ethanol and ultrasonically stirred for 90 min. Then, 400 g of 3-(methacryloyloxy)propyltriethoxysilane and 400 mL of NH3·H2O were added to the ethanol dispersion and stirred at 50 ° C for 6 h. The residue was filtered and washed twice with 2.0 L of anhydrous ethanol and dried under vacuum at 55 ° C to obtain the modified cyclodextrin metal framework material (M-β-CD-MOF-3).

[0079] 100 parts of trimethoxy-terminated 107 glue with a viscosity of 100000 mPa·s, 50 parts of dimethyl silicone oil with a viscosity of 100 mPa·s, 20 parts of M-β-CD-MOF-3, and 200 parts of heavy calcium carbonate were dehydrated and blended at a temperature of 90°C and a vacuum degree of -0.080 MPa for 180 minutes. After being fully cooled to 40°C, 1.5 parts of propyltrimethoxysilane, 0.2 parts of γ-aminopropyltrimethoxysilane and 2 parts of diisobutyl di(ethyl acetoacetate) titanate were added, and the mixture was mixed and reacted for 40 minutes at a vacuum degree of -0.095 MPa and a stirring speed of 800 rpm to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0080] Example 4

[0081] The difference between this embodiment and embodiment 1 is that α-cyclodextrin is used instead of γ-cyclodextrin, and the other preparation raw materials and reaction conditions of the cyclodextrin metal frame material and the dealcoholized silicone sealant composition are the same as those in embodiment 1.

[0082] 162g of α-cyclodextrin and 56g of potassium hydroxide were dissolved in 5.0L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 4.5L of methanol. After standing and diffusing at 50°C for 5h, 66.5mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 25°C for 12h. The solution was filtered, and the obtained crystals were washed twice with 1.5L of methanol, and then dried under vacuum at 50°C to obtain a cyclodextrin metal framework material (α-CD-MOF).

[0083] 60 g of α-CD-MOF was added to 2.0 L of anhydrous ethanol and ultrasonically stirred for 60 min. Then, 250 g of 3-(acryloyloxy)propyltrimethoxysilane and 200 mL of NH3·H2O were added to the ethanol dispersion, and the reaction was stirred at 70°C for 3 h. The residue was filtered and washed twice with 1.0 L of anhydrous ethanol and dried under vacuum at 60°C to obtain a modified cyclodextrin metal framework material (M-α-CD-MOF-4).

[0084] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 70 parts of M-α-CD-MOF-4, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0085] Example 5

[0086] The difference between this embodiment and embodiment 1 is that β-cyclodextrin is used instead of γ-cyclodextrin, and the other preparation raw materials and reaction conditions of the cyclodextrin metal frame material and the dealcoholized silicone sealant composition are the same as those in embodiment 1.

[0087] 162g of β-cyclodextrin and 56g of potassium hydroxide were dissolved in 5.0L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 4.5L of methanol. After standing and diffusing at 50°C for 5h, 66.5mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 25°C for 12h. The solution was filtered, and the obtained crystals were washed twice with 1.5L of methanol, and then dried under vacuum at 50°C to obtain a cyclodextrin metal framework material (β-CD-MOF).

[0088] 60 g of β-CD-MOF was added to 2.0 L of anhydrous ethanol and ultrasonically stirred for 60 min. Then, 250 g of 3-(acryloyloxy)propyltrimethoxysilane and 200 mL of NH3·H2O were added to the ethanol dispersion, and the reaction was stirred at 70°C for 3 h. The residue was filtered and washed twice with 1.0 L of anhydrous ethanol and dried under vacuum at 60°C to obtain a modified cyclodextrin metal framework material (M-β-CD-MOF-5).

[0089] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 70 parts of M-β-CD-MOF-5, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0090] Comparative Example 1

[0091] The difference between this comparative example and Example 1 is that the modified cyclodextrin metal frame material is not added to the dealcoholized silicone sealant composition, and the other preparation raw materials and reaction conditions of the dealcoholized silicone sealant composition are the same as those in Example 1.

[0092] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyl trimethoxy silane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyl trimethoxy silane and 4 parts of diisopropyl di(ethyl acetoacetate) titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a dealcoholized silicone sealant composition.

[0093] Comparative Example 2

[0094] The difference between this comparative example and Example 1 is that γ-cyclodextrin is used in equal amount to replace M-γ-CD-MOF-1, and other preparation raw materials and reaction conditions of the dealcoholized silicone sealant composition are the same as those in Example 1.

[0095] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 70 parts of γ-cyclodextrin, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a dealcoholized silicone sealant composition.

[0096] Comparative Example 3

[0097] The difference between this comparative example and Example 1 is that γ-CD-MOF is used in equal amount to replace M-γ-CD-MOF-1, and the other preparation raw materials and reaction conditions of the dealcoholized silicone sealant composition are the same as those in Example 1.

[0098] 162g of γ-cyclodextrin and 56g of potassium hydroxide were dissolved in 5.0L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 4.5L of methanol. After diffusing at 50°C for 5h, 66.5mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and allowed to stand at 25°C for 12h. The solution was filtered, and the obtained crystals were washed twice with 1.5L of methanol, and then dried under vacuum at 50°C to obtain a cyclodextrin metal framework material (γ-CD-MOF).

[0099] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 70 parts of γ-CD-MOF, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0100] The following performance tests were performed on the dealcoholized silicone sealant compositions prepared in Examples 1-5 and Comparative Examples 1-4:

[0101] 1. Surface drying time: Tested according to method B of GB / T 13477.5-2002 "Test methods for building sealing materials Part 5: Determination of surface drying time".

[0102] 2. 24h curing depth (mm) test: Take two square glass pieces with a side length of 50mm, clean the surface with ethanol and dry it, then put a glue ball on one of the glass pieces, press the other glass piece on the glue ball, make the upper and lower glass pieces parallel, and control the distance between them to be 6mm. Use a scraper to scrape away the overflowing glue around the edges of the two parallel glass pieces and ensure that the surface of the glue is flat. After curing the specimen in an environment of 23℃ and 50%RH for 24h, cut the glue along the parallel surface. After removing the uncured glue, measure the thickness of the cured glue around the edge of the specimen, and take the average value, which is the 24h curing depth value.

[0103] 3. Paintability: According to GB / T 9286-1998 standard, the adhesion of paint and sealant is tested by the 100-grid method.

[0104] The test results are shown in Table 1. It can be seen from Comparative Example 1 and Example 1 that the modified cyclodextrin metal frame material of the present invention can significantly improve the coating performance of the dealcoholized silicone sealant, and at the same time can significantly improve the storage stability of the dealcoholized silicone sealant and increase the deep curing speed, which can significantly shorten the surface drying time and increase the curing depth.

[0105] From the comparison between Comparative Example 2 and Comparative Example 1 and Example 1, it can be seen that cyclodextrin can also improve the storage stability of the dealcoholized silicone sealant and increase the deep curing speed to a certain extent, but its effect is far worse than that of the modified cyclodextrin metal frame material of the present invention. The dealcoholized silicone sealant added with the modified cyclodextrin metal frame material of the present invention has better storage stability and higher deep curing speed; and cyclodextrin cannot improve the paintability of the dealcoholized silicone sealant.

[0106] From the comparison between Comparative Example 3 and Example 1, it can be seen that compared with the unmodified cyclodextrin metal frame material, the modified cyclodextrin metal frame material can significantly improve the paintability of the dealcoholized silicone sealant, and can further improve the deep curing speed of the dealcoholized silicone sealant.

[0107] From the comparison of Examples 1, 4 and 5, it can be seen that the improvement effect of M-γ-CD-MOF-1 on the storage stability of dealcoholized silicone sealant is better than that of M-β-CD-MOF-1 and M-α-CD-MOF-1.

[0108] Table 1

[0109]

[0110]

[0111] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A modified cyclodextrin metal framework material, characterized in that: It is obtained by modifying the cyclodextrin metal framework material with silane containing acryloxy groups.

2. The modified cyclodextrin metal frame material according to claim 1, characterized in that: The acryloxy-containing silane is selected from at least one of 3-(acryloxy)propyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propyltriisopropoxysilane and methacryloxypropyltriacetoxysilane; and / or, The cyclodextrin in the cyclodextrin metal framework material is one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin.

3. The modified cyclodextrin metal frame material according to claim 1 or 2, characterized in that: The mass ratio of the acryloxy-containing silane to the cyclodextrin metal framework material is 2-6:1, preferably 3-5:1, and more preferably 3.5-4.5:

1.

4. The modified cyclodextrin metal frame material according to claim 1 or 2, characterized in that: The preparation method of the cyclodextrin metal frame material comprises the following steps: filtering an aqueous solution containing cyclodextrin and potassium hydroxide into a first alcohol solvent, allowing the solution to stand at 40°C-60°C for 4h-8h, adding hexadecyltrimethylammonium bromide, stirring evenly, and allowing the solution to stand at 20°C-30°C for 8h-24h to obtain the cyclodextrin metal frame material; Preferably, the mass ratio of cyclodextrin, potassium hydroxide and hexadecyltrimethylammonium bromide is 1g: 0.3g-0.4g: 0.2mg-0.6mg, preferably 1g: 0.2g-0.5g: 0.3-0.5mg; Preferably, the concentration of the cyclodextrin in the aqueous solution is 25 g / L to 40 g / L, preferably 30 g / L to 35 g / L; Preferably, the volume ratio of the first alcohol solvent to water is 1:0.8-1.2; Preferably, the first alcohol solvent is methanol or ethanol.

5. A method for preparing the modified cyclodextrin metal frame material according to any one of claims 1 to 4, characterized in that: The steps include: The cyclodextrin metal framework material is added to the second alcohol solvent and dispersed evenly, and then the acryloxy-containing silane and NH3·H2O are added, and the mixture is stirred and reacted at 50° C.-80° C. for 3 h-6 h to obtain the modified cyclodextrin metal framework material.

6. The method for preparing the modified cyclodextrin metal frame material according to claim 5, characterized in that: The second alcohol solvent is methanol or ethanol; and / or, The ratio of the cyclodextrin metal framework material and the second alcohol solvent is 1g:20mL-50mL, preferably 1g:30mL-40mL; and / or, The ratio of the cyclodextrin metal framework material to NH3·H2O is 1g:2mL-5mL, preferably 1g:3mL-4mL.

7. The method for preparing the modified cyclodextrin metal frame material according to claim 5 or 6, characterized in that: The steps include: The cyclodextrin metal framework material is added to anhydrous ethanol, ultrasonically stirred for 60 min-90 min, and then the silane containing acryloxy group and NH3·H2O are added, stirred and reacted at 50°C-80°C for 3h-6h, filtered, washed, and dried to obtain the modified cyclodextrin metal framework material; Preferably, the reaction is stirred at 65°C-75°C for 3h-4h; Preferably, the drying is carried out under vacuum conditions at 50°C-60°C.

8. A dealcoholized silicone sealant, characterized in that: The product is prepared from the following raw materials in parts by mass: 100 parts of alkoxy-terminated 107 glue; 20-50 parts of dimethyl silicone oil; 20-90 parts of the modified dextrin metal frame material according to any one of claims 1 to 4; Preferably, the dealcoholized silicone sealant is prepared from raw materials including the following components, in parts by mass:

9. The dealcoholized silicone sealant according to claim 8, characterized in that: The alkoxy-terminated 107 glue is at least one of methyl dimethoxy-terminated 107 glue, methyl diethoxy-terminated 107 glue, vinyl dimethoxy-terminated 107 glue, vinyl diethoxy-terminated 107 glue, trimethoxy-terminated 107 glue and triethoxy-terminated 107 glue; and / or, The viscosity of the alkoxy-terminated 107 glue at 25° C. is 10000 mPa·s to 100000 mPa·s, more preferably 15000 mPa·s to 25000 mPa·s; and / or, The viscosity of the dimethyl silicone oil at 25° C. is 100 mPa·s to 500 mPa·s, preferably 300 mPa·s to 400 mPa·s; and / or, The inorganic filler is at least one of nano-active calcium carbonate, light calcium carbonate and heavy calcium carbonate; and / or, The crosslinking agent is at least one of methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane and phenyltrimethoxysilane; and / or, The coupling agent is at least one of γ-aminopropyltrialkoxysilane, N-(β-aminoethyl)-γ-aminopropyltrialkoxysilane, γ-glycidyloxypropyltrialkoxysilane, γ-mercaptopropyltrimethoxysilane and 3-isocyanatepropyltrialkoxysilane; and / or, The titanate catalyst is selected from at least one of tetraisopropyl titanate, tetrabutyl titanate, diisopropyl di(ethyl acetoacetate) titanate, dibutoxy di(ethyl acetoacetate) titanate and diisobutyl di(ethyl acetoacetate) titanate.

10. A method for preparing the dealcoholized silicone sealant according to claim 8 or 9, characterized in that: The steps include: The alkoxy-terminated 107 glue, dimethyl silicone oil, modified cyclodextrin metal frame material and inorganic filler are dehydrated and blended at a temperature of 90°C to 130°C and a vacuum degree of -0.08MPa to -0.099MPa for 60min to 180min, cooled to 40°C to 50°C, and the cross-linking agent, coupling agent and catalyst are added. The mixture is mixed and reacted for 40min to 120min at a vacuum degree of -0.08 to -0.099MPa and a stirring speed of 100rpm to 800rpm to obtain the dealcoholized silicone sealant.